Effective use and exploitation of modern languages labs (2016)
The effective use and exploitation of modern languages labs wants to be reflected in this research within an educational institution. It is worth mentioning that the labs are appropriate places in order to support oral, written learning and listening comprehension of a language. As these places are useful for teachers and students, they must rely on suitable technological tools for this purpose. Ecci (Universidad Escuela Colombiana De Carreras Industriales) university, being a trainer institution in the modern languages program, it requires the use of information and communication technologies for the comprehensive teaching on English, French and German languages skills that is why these places must be adapted according to the legitimate needs of major and professional field.